Chiral Brønsted Acids Catalyze Asymmetric Additions to Substrates that Are Already Protonated: Highly Enantioselective Disulfonimide-Catalyzed Hantzsch Ester Reductions of NH–Imine Hydrochloride Salts - Wakchaure, Vijay N.; Obradors, Carla; List, Benjamin (Synlett, 2020)
While imines are frequently used substrates in asymmetric Brønsted acid catalysis, their corresponding salts are generally considered unsuitable reaction partners. Such processes are challenging because they require the successful competition of a catalytic amount of a chiral anion with a stoichiometric amount of an achiral one. We now show that enantiopure disulfonimides enable the asymmetric reduction of N–H imine hydrochloride salts using Hantzsch esters as hydrogen source. Our scalable reaction delivers crystalline primary amine salts in great efficiency and enantioselectivity and the discovery suggests potential of this approach in other Brønsted acid catalyzed transformations of achiral iminium salts. Kinetic studies and acidity data suggest a bifunctional catalytic activation mode.
Keywords: Brønsted acids; N–H imine hydrochloride salt; primary amine; disulfonimide (DSI); organocatalytic reduction